AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DI KECAMATAN DUMOGA BARAT KABUPATEN BOLAANG MONGONDOW TAHUN 2016 - Hamandu Mamonto (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This research focuses on the application of the principle of accountability in the management of the Village Funds Allocation for the purpose of describing the management accountability Village Funds Allocation. This research was conducted because Allocation Fund Executive Team Village in performing its financial administration not in accordance with applicable regulations. This research is expected to be beneficial to the Bolaang Mongondow district government, especially subdistrick Dumoga Barat in an effort to increase management accountability Village Fund Allocation. This research was conducted in villages in the subdistrict Dumoga Barat, as one implementaion location of the Village Fund Allocation. As the informant was elected Village Implementation Teams and the communities that are considered to represent the research unit in the management of the Village Fund Allocation. Research conducted in-depth interviews and direct observation by the implementation of the Village Fund Allocation. The results of this study indicate that for the planning and implementation activities of the Village Fund Allocation, has revealed the existence of management accountable and transparent. While accountability is seen in the physical results have shown the implementation of accountable and transparent, but from the administration still needed further development, because not fully in accordance with the provisions. The main constraint is not effective coaching village government officials and human resource competencies, so that still need assistance from local government officials on an ongoing basis.